Amyotrophic Lateral Sclerosis (ALS): Telemedicine system for home care and patient monitoring. Issue 1 (January 2019) - Fanella, G.; De Salvo, G.; Frasca, V.; Calamani, M.; Onesti, E.; Ceccanti, M.; Cucchiella, C.; Barone, T.; Pozzilli, V.; Fiorini, I.; Goglia, M.; Di Bari, S.; et al.
Abstract : The development of a new domotic healthcare system for patients with Amyiotrophic Lateral Sclerosis (ALS) to improve home-based clinical follow-up through the identification of functional loss worsening and complications, preserving interaction between patients and caregivers. The following electromedical wireless sensors were developed to analyse breathing, nutrition, motility and communication: Pulse Oximeter, surface EMG sensor associated to a dynamometer, Laryngophone, EEG-based BCI device. The project was divided into: (1) User centered design; (2) development of wireless sensors, remote terminal units, central server; (3) pilot clinical project and medical validation. Visual Analogic Scale (VAS) and SUS scales were used to analyse the user-friendliness and the satisfaction of each sensor. The domotic interface was tested on eight patients with ALS. SUS and VAS scores indicate a good system usability, both in satisfaction and in ease of use. The usability of the Laryngophone may be improved, even if ratings of recorded audiofiles performed well. The data collected, born from the collaboration between neurologists and biomedical engineers, led to innovative home medical devices and original algorithms that recognize alterations of vital parameters of patients with ALS at different degrees of disability, overcoming the current clinical follow-up deficit and giving patients a chance to recover interaction with environment.